MODEL DINAMIS RANTAI MAKANAN TIGA SPESIES - Pratikno, Wiji Budi; Sunarsih, Sunarsih (MATEMATIKA, 2010)
. Three species food chain models are model that express the interaction of three populations of prey, first predator and second predator populations. The models are derived from a combination of logistic growth model between prey population and predator population. Model that is used is a Holling type II functional response. The model consists of non linear differential equations with three dependent variables, there are  representing size of prey population at time ,  is size of  first predator population at time , and  is size of second predator population at time . From the result of stability analysis conducted on the food chain model of three species are found six equilibrium points based on the value eigen, and six cases of different stability.